1989
DOI: 10.1016/0020-7292(89)90815-1
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcome in unmarried teenage nulligravidae in Singapore

Abstract: Singapore, like other newly industralized countries, has seen a dramatic transformation in the social standards of its population in a particularly short space of time. Unfortunately, this period of development has been accompanied by an escalation in the number of pregnancies to unmarried teenage girls. This paper examines the obstetric and social implications of 150 such pregnancies in younger and older teenagers. Poor intrauterine growth in the younger teenager appears to be the most important adverse obste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Kurup AO et al [18], Lubarsky SL et al [19] also found the similar results as our study. In adolescent child bearing may have various causes and also girls physiologically not enough to become pregnant.…”
Section: Discussionsupporting
confidence: 91%
“…Kurup AO et al [18], Lubarsky SL et al [19] also found the similar results as our study. In adolescent child bearing may have various causes and also girls physiologically not enough to become pregnant.…”
Section: Discussionsupporting
confidence: 91%
“…(1) Nepal, (3) India, (5,12) Nigeria, (6) the United States (8) and Singapore, (13) it contradicts the results of previous studies conducted in Nepal (7) and Finland. (9) These studies, however, used different cutoff ages to define 'young maternal age'.…”
Section: Discussionmentioning
confidence: 73%
“…(13) However, that study did not evaluate the effect of maternal socioeconomic or behavioural factors on these outcomes. (13) Based on data from the Singapore National Birth Defects Registry report in 2000, extreme maternal age was found to be a significant risk factor for non-chromosomal birth defects, a major cause of perinatal mortality locally. (14) In particular, young mothers were found to have a higher risk of having a baby with gastroschisis, a congenital anterior abdominal wall defect.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations